Obesity and labor market outcomes - Susan L. Averett (IZA World of Labor, 2019)
Rising obesity is a pressing global public health problem responsible for rising health care costs and in some countries one of the leading causes of preventable deaths. There is substantial evidence that obese people are less likely to be employed and, when employed, earn lower wages. There is some evidence that the lower earnings are a result of discriminatory hiring and sorting into jobs with less customer contact. Understanding whether obesity is associated with adverse labor market outcomes and ascertaining the source of these outcomes are essential for designing effective public policy.
Keywords: J7; J78; J71; 330; obesity; BMI; wages; employment; occupation; absenteeism